New ways to classify bipolar disorders: going from categorical groups to symptom clusters or dimensions - Henry, Chantal (Current Science, 2010)
Current psychiatric disorders classifications are based exclusively on categorical models, which were designed to increase the reliability of the diagnosis. However, this system has some limitations and various psychiatric disorders may be classified using a dimensional approach, which is more appropriate when no clear boundaries exist between entities or when examining various features on a continuum. Thus, the forthcoming DSM-V appears to undertake a hybrid approach, by including categorical models associated with dimensions. We aimed to review examples of dimensions or symptom clusters, associated with a categorical approach, which could be useful in refining bipolar disorder classification. We selected predominant polarity, psychotic symptoms, inhibition/activation behavioral level and emotional reactivity to define mood episodes, impulsivity/suicidality/substance misuse and cognitive impairment. The selection was based on the fact that these dimensions or symptom clusters are currently discussed to be implemented in the DSM-V and/or may orientate towards the choice of specific treatments and represent more homogeneous and thus more appropriate sub-groups for research purpose. In the future, there will be a need to identify biomarkers that can definitively validate the use of these criteria.